Assessment of African patients with fragility fractures in the orthopaedic department at Chris Hani Baragwanath academic hospital - Thomas, Preetha (My University, 2017)
BACKGROUND: The aim of the study was to assess whether African subjects with fragility fractures were being identified for assessment for osteoporosis on presentation to the orthopaedic department at Chris Hani Baragwanath Academic Hospital (CHBAH) in Soweto. In addition, the recommendation for secondary prevention of disease for these subjects, was also assessed. METHOD: One hundred African subjects over the age of 50 years with fragility fractures were identified in the orthopaedic wards and clinics at CHBAH. These subjects were interviewed with two separate questionnaires addressing risk factors and education regarding osteoporosis, and whether further management was suggested. The first interview was conducted in June and July 2015. After 18 months, a follow up telephonic interview was conducted, in December 2016, with 37 of the original 100 subjects. RESULTS: Of the 100 subjects evaluated, 89 (89%) were asked at least one screening question. The most frequently asked question about risk factors for osteoporosis in the first interview, was regarding previous fractures and was asked of 61 (61%) of the 100 subjects. A further 37 (37%) of all subjects had been given advice regarding appropriate bone strengthening exercises to prevent osteoporosis. Only five subjects (5%) were asked to return for further assessment. The second interview showed that the most frequently asked question was regarding previous fractures in 24 (64.9%) of the 37 subjects and 18 (48.6%) of the 37 subjects had been advised to do bone strengthening exercises. Only two (5.4%) new subjects could confirm receiving a date to return for assessment. CONCLUSION: In this study, orthopaedic surgeons were proven to be inadequately assessing risk factors for osteoporosis and were infrequently referring patients for therapy. Orthopedic surgeons are often the only practitioners to see patients with fragility fractures and thus they have a crucial role in identifying and appropriately referring these patients for further investigations and medical management for osteoporosis.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Medicine (MMed). Johannesburg 2017
Keywords: Orthopaedics; Osteoporosis; Fractures